2020
DOI: 10.1111/poms.13166
|View full text |Cite
|
Sign up to set email alerts
|

Unintended Consequences of Automated Vehicles and Pooling for Urban Transportation Systems

Abstract: Automated vehicles (AVs) have emerged rapidly in recent years, becoming a focus of high expectations and heated debates. Advocates argue that the arrival of AVs will make driving safer, greener, cheaper, and faster, bringing ubiquitous access to transportation while significantly reducing traffic congestion and environmental impacts. Skeptics, in contrast, suggest that the appeal of AVs will induce additional driving, offsetting or even overwhelming the positive effects of increased automation. Many analysts n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 40 publications
0
34
0
1
Order By: Relevance
“…The study by Tan et al (2017) in China found that enforcing environmental regulations often exacerbated opportunistic behavior at the expense of other stakeholders. The study by Naumov et al (2020) on automated vehicles found that carpooling initiatives could actually unintentionally result in making traffic congestion worse. Zarei et al (2019) found that even humanitarian supply chains have unintended consequences, where for example detrimental environmental outcomes are often neglected.…”
Section: Unanticipated Outcomes In the Quest For Sustainabilitymentioning
confidence: 99%
“…The study by Tan et al (2017) in China found that enforcing environmental regulations often exacerbated opportunistic behavior at the expense of other stakeholders. The study by Naumov et al (2020) on automated vehicles found that carpooling initiatives could actually unintentionally result in making traffic congestion worse. Zarei et al (2019) found that even humanitarian supply chains have unintended consequences, where for example detrimental environmental outcomes are often neglected.…”
Section: Unanticipated Outcomes In the Quest For Sustainabilitymentioning
confidence: 99%
“…Even though disruptive technologies, such as self‐driving cars, V2X communication, and electric vehicles, will eventually mature to the point that everyone can use them, they will also cause inevitable increases in traffic demand (Naumov et al. 2020, Qi and Shen 2019). Given these circumstances, sustainable mobility strategies should be used to motivate private car users to choose low‐emission travel modes, such as public transport, to reduce the negative effects of transportation systems on transportation infrastructure and the environment.…”
Section: Introductionmentioning
confidence: 99%
“…When production and operations management entered the era of Industry 4.0, innovations of digital technologies and automation technologies, such as cloud computing (Arbabian et al 2021), AI and machine learning (Simester et al 2020), blockchain (Babich and Hilary 2020), data analytics (Choi et al 2018), and autonomous vehicles (Naumov et al 2020), have reshaped many industries (Dai et al 2020) and have caught scholars' attention.…”
Section: Technology Innovationmentioning
confidence: 99%